Quantification of light-promoted conidiation of Neurospora crassa bd, al-2 using a video system and densitometry software - Josef Maier; Helga Ninnemann (Fungal Genetics Reports, 1996)
Quantification of conidia from Neurospora crassa mycelia grown on solid media by turbidity assay or weighing of conidia is difficult. We demonstrate here measurement of the intensity of light-promoted conidiation bands of Neurospora crassa strain albino-band (al-2, bd) using a video image system and densitometry software.